The Right of Property in Albania and Approach to Legislation Section 1 Prot 1 to the ECHR - Petanaj, Enkeleida (Richtmann Publishing, 2012)
The right of property is regarded as one of human rights, even an absolute right. It is certain that ownership is a legalinstitution around which revolve yet been developed and today a series of debates and political battles. Certain forces could playpolitically to the right of property making the vehicle thereby leading to victory. It is considered a fundamental right and beneficial on theone hand, and on the other as a borderline between different social strata, and social injustice. The right of property in various legalorders has had a different defense. In countries with a democratic regime, its defense is given a special importance because it isconsidered as the basic condition for creating and ensuring a better status in the personal economy of different subjects and then at thenational and international. But with all the legislative measures taken by the Albanian state, the legal status of property rights in Albanialeaves much to be desired. It is also used as the main argument of the parties during their political campaign to obtain political office. Inthis way the legislative measures taken by the Albanian national state was born the need for Albania to obtain commitments at theinternational level, subject to the objectives of our state to participate in the large European family. Albania has had time to provide alegal standard and it will need even more time and commitment to implement them this fact.